Romeiros e devotos do padre Cícero: investigação psicanalítica de processos psicológicos da vida religiosa - Luz, Karla Daniele de Sá Maciel (2012)
With the passage of time, religion, in its vast gamut of meanings has piqued, and continues to increasingly pique the interest of researchers from the most varied areas of study. One of these areas is psychoanalysis, starting with Freud himself. His work provides us with countless contributions to the understanding of this phenomenon, religion. His contributions range from a more scientific discourse, to a discourse of an analytical nature, to new ways of theorizing about religious experience. Some aspects of popular religiosity, for example, have been highlighted as subjects of research, by both psychology and psychoanalysis. Among the various manifestations of popular piety, we have here in Brazil the pilgrims of Padre (Father) Cicero. This manifestation is characterized by pilgrimages and worship of the image of the priest Padre Cicero Romão Batista, by people from the backlands of the Northeast. Every year, at certain times, crowds of people head for the city of Juazeiro for the blessings of Padim Ciço , as they call him. The objective of this study was to investigate the psychological processes underlying the religious beliefs of the pilgrims and devotees of Padre Cicero to the extent that these were known. This study was conducted by observation through participation and by collecting testimonies, which were put into dialogue with the support of Freudian metapsychology theory. This research enabled the construction of reflections on transference in the process of research in psychoanalysis, understanding of the representation of familiar figures in religious emblems and the subliminal process of drives as related to the experience of faith. With this method we sought not only to better understand the psychic organization when influenced by religious experience, but to also reflect on both research in psychoanalysis and phenomena in Brazilian culture